2009
DOI: 10.1007/s11426-009-0148-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of combined substitution of Dy and Mo or Si on the crystal structures and magnetic properties of Nd1−y Dy y Fe11−x TiM x (M = Mo, Si) compounds

Abstract: A series of Nd 1−y Dy y Fe 11−x TiM x (M = Mo, Si) alloys have been prepared by arc melting and studied by X-ray diffraction and neutron diffraction. All samples are found to crystallize in the ThMn 12 -type structure. The lattice parameters a and c and unit cell volume V of Nd 0.5 Dy 0.5 Fe 11−x TiMo x alloys increase linearly with increasing content of Mo (x), while the lattice parameters a and c and unit cell volume V of Nd 0.5 Dy 0.5 Fe 11−x TiSi x alloys decrease linearly with increasing content of Si(x).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…These studies also showed that an amino acid prodrug bound to Silybin resulted in an improvement in water solubility. 23) Biasutto et al 24) and Mulholland et al 25) used quercetin as a raw material to make amino acid derivatives to increase the bioavailability.…”
mentioning
confidence: 99%
“…These studies also showed that an amino acid prodrug bound to Silybin resulted in an improvement in water solubility. 23) Biasutto et al 24) and Mulholland et al 25) used quercetin as a raw material to make amino acid derivatives to increase the bioavailability.…”
mentioning
confidence: 99%
“…The light wavelength used is therefore crucial; although light penetration also depends on the type of tissue irradiated, [73] it is generally accepted that the UV-to-blue-light range shows the lowest ability to penetrate tissues, while NIR has the highest penetration. [74] Many tumors can reach large sizes (≥ 1 cm), [75][76][77][78] making the absorption of light at high wavelengths essential, and the NIR window (700-1100 nm) is the best spectral range to cure large and deep-seated tumors. To date, the number of NIR-absorbing PSs is small and UV/VISabsorbing PSs are being used to treat superficial or very small tumors.…”
Section: Ii13 Nanoparticles For Light Conversion and The Treatment Of...mentioning
confidence: 99%
“…[9] The power density of postfilament is lower than the self-focusing critical power, and the 124209-4 diffraction and dispersion effects are stronger than the selffocusing effect. The laser beam is in a divergent state, [32] and its spectral stability is lower than pre-filament area. Therefore, the spatial distribution of the quantitative analysis parameters is not uniform.…”
Section: Rsdmentioning
confidence: 99%